2017
DOI: 10.29252/ijrm.15.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Association of -460C/T and +405 G/C polymorphisms of vascular endothelial growth factor gene and susceptibility of ovarian hyperstimulation syndrome

Abstract: Background:Ovarian hyperstimulation syndrome (OHSS) is one of the most important complications of assisted reproduction treatment. Many substances are involved in the regulation of the vascular permeability, which have been concerned to cause OHSS. Vascular endothelial growth factor (VEGF) has emerged as one of the main angiogenic factors, which could be responsible for increased vascular permeability.Objective: In this study the association of vascular endothelial growth factor -460C/T and +405 G/C polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…If the implication of VEGF in the development of OHSS is indisputable, the part this factor is playing in triggering these severe forms is less clear. In this context, many studies have indicated that the development of severe forms of disease requires the implication of adjuvant factors, such as certain VEGF (19) or VEGF receptor polymorphisms (VEGFR1-519 and VEGF-405) (20), cytokines (interleukin (IL) 2, IL6, IL8) or cytokine signaling (SOCS) proteins (21) and, last but not least, certain factors involved in angiogenesis (Pigment Epithelium-Derived Factor) (PEDF) (22). This is also the case of severe OHSS forms occurring in patients undergoing VEGF receptor blockers therapy.…”
Section: Discussionmentioning
confidence: 99%
“…If the implication of VEGF in the development of OHSS is indisputable, the part this factor is playing in triggering these severe forms is less clear. In this context, many studies have indicated that the development of severe forms of disease requires the implication of adjuvant factors, such as certain VEGF (19) or VEGF receptor polymorphisms (VEGFR1-519 and VEGF-405) (20), cytokines (interleukin (IL) 2, IL6, IL8) or cytokine signaling (SOCS) proteins (21) and, last but not least, certain factors involved in angiogenesis (Pigment Epithelium-Derived Factor) (PEDF) (22). This is also the case of severe OHSS forms occurring in patients undergoing VEGF receptor blockers therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Se han demostrado altas concentraciones de VEGF en líquido ascítico de pacientes con síndrome de hiperestimulación ovárica (27) y varios estudios han demostrado concentraciones elevadas de VEGF en el suero y el líquido folicular de mujeres con síndrome de hiperestimulación ovárica (28)(29)(30) . Tanto el líquido folicular como peritoneal de pacientes con alta respuesta a hiperestimulación ovárica controlada muestran aumento significativo en la tasa de permeabilidad a través de células endoteliales in vitro (31) .…”
Section: Mientras Que Los Folículos Preantralesunclassified
“…To investigate if rare variants potentially involved in the development of OHSS were present, variants called in the 12 cases with OHSS were filtered using a predefined in silico gene panel including 76 genes predisposing to OHSS (Online Resource 2). The genes included in the gene panel were selected based on an extensive literature search in PubMed and Online Mendelian Inheritance in Man (OMIM) and were implicated in controlled ovarian stimulation response, associated with OHSS or regulation of gonadotropin action and/or ovarian angiogenesis [3,14,[16][17][18][19][20][21][22][23][24]. The gene panel included both known disease-associated genes related to OHSS and candidate genes which association with OHSS needs further study.…”
Section: Analysis I: In Silico Gene Panelmentioning
confidence: 99%